Development of a novel single channel arteriole microphysiological system for characterizing leukocyte-endothelial interactions - Sebastian Piombo; Christopher J. Hatch; Chauncey G. Evangelista; Shlomit Radom-Aizik; Dan M. Cooper; Christopher C.W. Hughes (Journal of Clinical and Translational Science)
Abstract